2015
DOI: 10.1186/s13063-015-0554-z
|View full text |Cite
|
Sign up to set email alerts
|

A mindfulness-based stress management program and treatment with omega-3 fatty acids to maintain a healthy mental state in hospital nurses (Happy Nurse Project): study protocol for a randomized controlled trial

Abstract: BackgroundIt is reported that nursing is one of the most vulnerable jobs for developing depression. While they may not be clinically diagnosed as depressed, nurses often suffer from depression and anxiety symptoms, which can lead to a low level of patient care. However, there is no rigorous evidence base for determining an effective prevention strategy for these symptoms in nurses. After reviewing previous literature, we chose a strategy of treatment with omega-3 fatty acids and a mindfulness-based stress mana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 68 publications
(70 reference statements)
1
36
0
2
Order By: Relevance
“…The connection between nurse wellbeing, compassion and enhanced patient care are also pertinent to this study. It has been suggested that nurses need to work in a compassionate environment that is conducive to caring (Boorman, 2010) and that mindfulness based training program can result in enhanced quality care for inpatients (Watanabe et al, 2015). The promotion of health and wellbeing among health care staff and the positive impact it can have on the quality of patient care was reflected in the United Kingdom policy document entitled Compassion in Practice (Department of Health, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The connection between nurse wellbeing, compassion and enhanced patient care are also pertinent to this study. It has been suggested that nurses need to work in a compassionate environment that is conducive to caring (Boorman, 2010) and that mindfulness based training program can result in enhanced quality care for inpatients (Watanabe et al, 2015). The promotion of health and wellbeing among health care staff and the positive impact it can have on the quality of patient care was reflected in the United Kingdom policy document entitled Compassion in Practice (Department of Health, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Nursing is considered a high‐risk, high‐pressure profession, given the fast‐paced working environment and constant need to handle emergencies. Thus, nurses are considered susceptible to psychological stress and mental health problems (Watanabe et al, ), perhaps making them more vulnerable to burnout than other healthcare professions (Maslach et al, ; Raftopoulos et al, ). Jamal and Baba () previously reported that job stress explained 50–80% of psychosomatic or stress‐related diseases among employees.…”
Section: Introductionmentioning
confidence: 99%
“…This particular quality of awareness has been associated with several indicators of physical and psychological health, and can be developed using specific techniques (mindfulness practices) commonly delivered in mindfulness-based interventions (MBIs; Demarzo et al, 2014 ). MBIs might not only lead to the maintenance of a healthy mental state in health workers, but also to a better quality of care for patients (Watanabe et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%